2022
DOI: 10.3389/fmicb.2022.1048457
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the accuracy of 11 different diagnostic tests for the detection of Schistosomiasis mansoni in individuals from a Brazilian area of low endemicity using latent class analysis

Abstract: BackgroundSchistosomiasis is a parasitic disease associated with poverty. It is estimated that 7.1 million people are infected with Schistosoma mansoni in Latin America, with 95% of them living in Brazil. Accurate diagnosis and timely treatment are important measures to control and eliminate schistosomiasis, but diagnostic improvements are needed to detect infections, especially in areas of low endemicity.MethodologyThis research aimed to evaluate the performance of 11 diagnostic tests using latent class analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…This is likely due to the appearance characteristic of Schistosoma eggs by microscopy. Likewise, KK showed a higher specificity than CCA in other LCA studies 10 12 , 14 18 , 28 . Moreover, recent studies have raised concerns that CCA may have low specificity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This is likely due to the appearance characteristic of Schistosoma eggs by microscopy. Likewise, KK showed a higher specificity than CCA in other LCA studies 10 12 , 14 18 , 28 . Moreover, recent studies have raised concerns that CCA may have low specificity.…”
Section: Discussionmentioning
confidence: 70%
“…A series of studies have evaluated the test performances of CCA and KK as well as the infection prevalence in S. mansoni using LCA 10 , 28 , despite a lack of previous research on S. japonicum . Some LCA models incorporated test results not only from KK and CCA but also from other methods such as ELISA 11 , 12 , polymerase chain reaction (PCR) 12 15 , circulating anodic antigen (CAA) 9 , 16 , DNA TaqMan 17 , and loop-mediated isothermal amplification (LAMP) 12 together.…”
Section: Discussionmentioning
confidence: 99%
“…For localities in the process of eliminating transmission, where the predictive values of serological tests are compromised given the low incidence of the disease, and since no single diagnostic test is capable of accurately detect schistosomiasis in this epidemiological scenario, FioSchisto endorses the two-step diagnostic strategy recommended by WHO. It is suggested that the first screening stage should be performed using commercial serological tests with high sensitivity and the second stage should use a molecular test, such as quantitative Polymerase Chain Reaction (qPCR) (54), which, despite being more complex, have higher sensitivity compared to Kato-Katz method and a higher level of specificity. It is worth noting that the COVID-19 pandemic has shown that Brazil has the infrastructure needed to perform molecular tests, improving diagnosis and reducing costs if implemented on a larger scale.…”
Section: Recommendations From Fioschistomentioning
confidence: 99%
“…In addition to conventional parasitological diagnostics, there are a number of other diagnostic methods available for the detection of schistosome infections (4)(5)(6)(7)(8). Improved coprological tests, such as the saline gradient method (9), formalin-ethyl acetate sedimentationdigestion (FEA-SD) (10) and Helmintex method (i.e., isolates eggs from fecal samples with the use of paramagnetic particles in a magnetic field) (11) showed an increased diagnostic sensitivity compared with the traditional techniques; yet are usually labour-intensive and have a lengthy processing time.…”
Section: Introductionmentioning
confidence: 99%